2012
DOI: 10.1111/j.1439-0507.2011.02166.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the peptide nucleic acid fluorescence in situ hybridisation technology for yeast identification directly from positive blood cultures: an Italian experience

Abstract: Fungaemia is an increasing nosocomial pathology. The 'gold standard' for detection of fungaemia is blood culture, but it is time-consuming and its sensitivity for early detection is low. On the other hand, yeasts present different antifungal sensitivity patterns to be quickly detected to allow an effective treatment. The aim of this study was to evaluate the diagnostic performances of PNA-FISH to directly identify yeasts from blood cultures and to compare results with those obtained by culture. A total of 176 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…The most successful method was the PNA‐FISH YTL assay achieving 96% (48/50) success. These findings are supported by two further studies publishing 96% and 99.3% success rates . Gram's stain analysis identified 72% (36/50) of the yeast isolates.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The most successful method was the PNA‐FISH YTL assay achieving 96% (48/50) success. These findings are supported by two further studies publishing 96% and 99.3% success rates . Gram's stain analysis identified 72% (36/50) of the yeast isolates.…”
Section: Discussionsupporting
confidence: 68%
“…These findings are supported by two further studies publishing 96% and 99.3% success rates. 27,28 Gram's stain analysis identified 72% (36/50) of the yeast isolates. MALDI-TOF MS identified 56% (28/50) using manufacturers log score thresholds for blood culture analyses increasing to 76% (38/50) when inhouse parameters were applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Italian study also showed that out of 176 candidemias, the YTL was rapid by 3 days and was accurate [70]. Another study showed that the YTL improved the accuracy of antifungal therapy from 76 to 95%, but only showed minimal antifungal cost savings and no impact on hospital length of stay [71].…”
Section: Candidamentioning
confidence: 99%
“…Recently, molecular methods such as real-time PCR and peptide nucleic acid fluorescent hybridization probes have become important tools for the detection of fungal pathogens in the clinical microbiology laboratory (4)(5)(6)(7). Although these methods can significantly reduce the turnaround time (TAT) for results, they require the clinician to make an educated guess as to the potential cause of infection since they often target only a single pathogen or a small group of related pathogens (8).…”
mentioning
confidence: 99%